A Pecking Order Theory of Capital Inflows and International Tax Principles - Yuen, Chi-Wa (IMF Working Papers; Working Paper ;, 1996)
Even though financial markets today show a high degree of integration, the world capital market is still far from the textbook story of high capital mobility. The purpose of this paper is to highlight key sources of market failure in the context of international capital flows and to provide guidelines for efficient tax structure in the presence of capital market imperfections. The analysis distinguishes three types of international capital flows: foreign portfolio debt investment, foreign portfolio equity investment, and foreign direct investment. The paper emphasizes the efficiency of a nonuniform tax treatment of the various vehicles of international capital flows.